Supply Chain Analysis and Local Beef Cattle Competitiveness in South Sulawesi - Palmarudi Mappigau; Jusni Ambo Upe; Kasmiati Kasim (Badan Pengelola Usaha (BPU) Universitas Jambi, 2023)
The purpose of this study is to analyze the relationship between supply chain and the competitiveness of native beef cattle in South Sulawesi Province. A conceptual model was developed to examine how supply chain, including : strategic supplier partnerships, market information sharing, knowledge technology in beef cattle production sharing are related to the competitiveness of native beef cattle. A survey questionnaire based on 64 farmers and intermediary traders from Bone Regency, South Sulawesi Province conducted to collect empirical data for testing the formulated hypothesis. Spearman's correlation coefficient analysis was conducted to test the hypothesized relationship. The study result showed that strategic supplier partnerships have a significant and positive relationship with competitive native beef cattle, while market share of information and knowledge technology in beef cattle production was not significant and positively associated with competitive native beef cattle. The study limitations/implications is other important dimensions for supply chain partnerships, namely information sharing, goal congruence, decision synchronization, incentive alignment, and resource sharing should also be involved for future research. Since this study was limited to the province of South Sulawesi, the findings of this study cannot be generalized to supply chain practices in Indonesia and developing countries. Therefore future research should be carried out in other provinces in Indonesia or in other developing countries